Diffusion‐Weighted Imaging Distinguishes Between Osteomyelitis, Bone Marrow Edema, and Healthy Bone on Forefoot Magnetic Resonance Imaging. Issue 5 (1st February 2022) - Kruk, Konrad A.; Dietrich, Tobias J.; Wildermuth, Simon; Leschka, Sebastian; Toepfer, Andreas; Waelti, Stephan; Kim, Chan‐Hi Olaf; Güsewell, Sabine; Fischer, Tim
Abstract : Background: Diagnosis of osteomyelitis by imaging can be challenging. The feasibility of diffusion‐weighted imaging (DWI) as ancillary sequence was evaluated in this study. Purpose: To evaluate DWI for differentiation between osteomyelitis, bone marrow edema, and healthy bone on forefoot magnetic resonance imaging (MRI). Study type: Prospective. Subjects: A total of 60 consecutive patients undergoing forefoot MRI divided into three study groups (20 subjects each): osteomyelitis, bone marrow edema, and healthy bone. Field strength/Sequence: A 1.5T and 3T MRI scanners; readout‐segmented multishot echo planar DWI. Assessment: Two independent radiologists measured apparent diffusion coefficient (ADC) values within abnormal or healthy bone. Statistical Tests: ADC values were compared between groups (pairwise t ‐test with Bonferroni‐Holm correction for multiple testing). Intraclass correlation coefficient (ICC) was calculated to assess inter‐reader agreement. Threshold ADC values were determined as the cutoffs that maximized the sum of sensitivity and specificity. Receiver operating characteristic (ROC) analysis was performed with statistical threshold of P  < 0.05. Results: Inter‐reader agreement was 0.92 in the healthy bone group and 0.78 in both the edema and osteomyelitis groups. Average ADC values were significantly different between groups: 1432 ± 222 × 10 −6  mm 2 /sec (osteomyelitis), 1071 ± 196 × 10 −6  mm 2 /sec (bone marrow edema), and 277 ± 89 × 10 −6  mm 2 /sec (healthy bone). A threshold ADC value of 534 × 10 −6  mm 2 /sec distinguishes between healthy and abnormal bone with specificity and sensitivity of 100% each. For distinction between osteomyelitis and bone marrow edema, two cutoff values were determined: a 95%‐specificity cutoff indicating osteomyelitis (>1320 × 10 −6  mm 2 /sec) and a 95%‐sensitivity cutoff indicating bone marrow edema (<1155 × 10 −6  mm 2 /sec). Diagnostic accuracy of 95% was achieved for 73% (29/40) of the subjects. Data Conclusion: DWI with ADC maps distinguishes between healthy and abnormal bone on forefoot MRI. Calculated cutoff values allow confirmation or exclusion of osteomyelitis in a high proportion of subjects. Evidence Level: 2 Technical Efficacy: Stage 2